The Influence Of Competence And Work Environment On The Performance Of Family Planning Counselors (PKB) In Surabaya City With Work Motivation As An Intervening Variable - Mardiana, Mira; Wardoyo, Dewie Tri Wijayati; Kistyanto, Anang (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This study investigates the influence of competence and the work environment on the performance of Family Planning Counselors (PKB) in Surabaya, with motivation as a mediating variable. It aims to identify critical factors impacting PKB performance and provide recommendations for improvement. Design/methodology/approach: The study employed Structural Equation Modeling-Partial Least Squares (SEM-PLS) to analyze data collected from 38 PKBs in Surabaya. Data were processed using SmartPLS 4, focusing on the relationships between competence, the work environment, motivation, and performance. Findings: Competence and the work environment do not significantly influence performance directly. However, both variables significantly impact performance indirectly through motivation, with mediating effects of 64.6% and 16.8%, respectively. Motivation emerged as a critical factor in enhancing performance, emphasizing the need for holistic development strategies. Research limitations/implications: The study is limited to PKBs in Surabaya, and the findings may not be generalizable to other regions or sectors. Future research should explore additional variables and broader samples. Practical implications: Organizations should prioritize motivational strategies, competency development, and supportive work environments to enhance employee performance effectively. Originality/value: This study highlights the mediating role of motivation in linking competence and the work environment to performance, providing insights into optimizing human resource strategies for public service organizations. Paper type: Research Paper